2005
DOI: 10.1056/nejmoa043876
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Intensive Lipid-Lowering Therapy in Calcific Aortic Stenosis

Abstract: Intensive lipid-lowering therapy does not halt the progression of calcific aortic stenosis or induce its regression. This study cannot exclude a small reduction in the rate of disease progression or a significant reduction in major clinical end points. Long-term, large-scale, randomized, controlled trials are needed to establish the role of statin therapy in patients with calcific aortic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
489
3
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 957 publications
(520 citation statements)
references
References 37 publications
14
489
3
14
Order By: Relevance
“…In the SALTIER trial, 155 patients with asymptomatic aortic valve calcium deposits were followed for 25 months 40. LDL levels were lowered by 53% in the treatment arm, but no differences in aortic‐jet velocity were identified.…”
Section: Discussionmentioning
confidence: 99%
“…In the SALTIER trial, 155 patients with asymptomatic aortic valve calcium deposits were followed for 25 months 40. LDL levels were lowered by 53% in the treatment arm, but no differences in aortic‐jet velocity were identified.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Mendelian randomization study also suggests a causal association between elevated LDL‐C and incidence of AS 15. However, three randomized clinical trials failed to demonstrate any significant effect of statins to reduce the progression rate of AS or the occurrence of valve‐related events, despite important reduction in LDL‐C level 16, 17, 18. Hence, it has been hypothesized that LDL‐C could be involved mainly in the initiation and early stages of the disease but has less influence in the more advanced stages.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is also significant because it provides a new and important therapeutic strategy for AVF. Recent clinical trials showed that statin failed to attenuate the progression of aortic stenosis (Cowell et al ., 2005; Houslay et al ., 2006; Rossebo et al ., 2008; Chan et al ., 2010), suggesting that antihyperlipidemia therapy alone is insufficient for treatment of the disease. The findings from the current study suggest that pharmacological activation of AMPKα should be tested for treating FAVD.…”
Section: Discussionmentioning
confidence: 99%